Passage to Marseille - Nordhoff, Charles 1887-1947; Hall, James Norman 1887-1951; Steiner, Max 1888-1971 (Warner Bros. Entertainment, 2024)
"In einer komplizierten Rückblende wird erzählt, wie ein glühender französischer Patriot vom journalistischen zum militärischen Engagement kam. Actionfilm, dessen technische Brillanz vom austauschbaren Gut-Böse-Schema ablenkt; das Handeln ist emotional motiviert, nicht politisch. Regisseur Michael Curtiz versammelt einen Teil der "Casablanca"-Besetzung erneut um sich." [filmdienst.de]
Original: USA 1944
Hard impact special features: Warner night at the movies 1944 short subjects gallery: vintage newsreel, Oscar-winning patriotic short I won't play, Oscar-nominated musical short Jammin' the blues, classic cartoon The weakly reporter, trailers of Passage to marseille and 1944's Uncertain glory ; new featurette The Free French: unsung victors ; breakdowns of 1944: studio blooper reel
Keywords: Film; Blu-Ray-Disc